Structural Insight into Chitosan Supports Functionalized with Nanoparticles - J. Lamarra; L. Damonte; S. Rivero; A. Pinotti (Advances in Materials Science and Engineering)
The incorporation of suspensions of nanoparticles functionalized with gallic acid (GA) was used as a strategy to obtain nanocomposite active films with different both chitosan : tripolyphosphate (CH : TPP) and nanoparticles:chitosan (N : CH) ratios. The thermal analysis carried out by modulated differential scanning calorimetry (MDSC) allowed observing the shift of an endothermic event towards higher temperatures with a greater N : CH ratio. Analyzing ATR-FTIR spectra through principal component analysis (PCA) can be inferred that the incorporation of the nanoparticles produced a discrimination of the samples into clusters when the region 1400–1700 cm−1 was considered. The decrease in crystalline size with the inclusion of nanoparticles (NA and NB) proved the existence of interactions among CH, TPP, and GA, resulting in a more amorphous structure. The positron annihilation lifetime spectroscopy (PALS) technique was adequate to correlate the glass transition temperatures (Tg) obtained by using the MDSC technique with parameters τ2 and I2 ascribed to the annihilation of positrons in the interface. The cross section of nanocomposites obtained by scanning electron microscopy (SEM) clearly showed a homogeneous distribution of the nanoparticles without aggregation, suggesting their compatibility with the CH matrix. By virtue of the obtained results, the nanocomposites with the greatest nanoparticle proportion and the highest TPP concentration attained significant modifications in relation to CH matrices because of the crosslinking of the biopolymer with GA and TPP.